BURUNG SEBAGAI ATRAKSI EKOWISATA DI KAWASAN PARIWISATA UBUD, BALI - A.A.G Raka Dalem; I N Widana; I.A Trisna Eka Putri (Environmental Research Center (PPLH) of Udayana University, 2014)
Research on “Birds as an Ecotour Attraction in Ubud Tourist Resort, Bali” (Burung sebagaiAtraksi Ekowisata di Kawasan Pariwisata Ubud, Bali) was undertaken in 2013. Aims ofthese research were as follows: first, to find out birds observed in Ubud Tourist Resort, Baliand second, to find out their potentials as ecotour attractions.Samples were collected by exploring the study sites and running interview between July andOctober, 2013. Observation was carried out by using binoculars and number of individualsof birds was counted by using a counter when necessary. Birds were identified such asthrough direct observation on the species, or through their calling. Results of observationwere compared with hand boooks, such as Mackinnon (1990) and Mackinnon et al. (1992).Birds data were recorded either on their species and on numbers (relative)/freqency, and theresult was typed in tables. The data provided such as the status (protected/not), migrantspecies or not, as well as their distribution. In addition, locations where birds have beenused as a tour attraction (ecotour attraction - bird watching), and how to set up theirproducts were reported.From this research it can be concluded as follows. In Ubud tourist resort at least 67 birdspecies have been identified, in which 7 (seven) were birds that were restricted theirdistribution in Indonesia, namely: Halcyon cyanoventris, Alcedo caerulescens, Paddaoryzivora, Prinia familiaris, Treron griseicauda, Dicaeum trochileum, and Gallus varius.In addition, from this reserach it was observed seven species of migrating birds: Hirundorustica, Merops philippinus or M. superciliosus, Accipiter soloensis, Actitis hypoleucos,Tringa glareola, Gallinago stenura, and Apus pacificus.From all birds observed, there were 14 species that were classified as protected species inIndonesia, namely: Sturnus melanopterus, Anhinga melanogaster, Bubulcus ibis, Egrettaalba, Egretta garzatta, Egretta intermedia, Halcyon cyanoventris, Halcyon chloris, Alcedocaerulescens, Haliastur indus, Nectarinia jugularis, Anthreptes malacensis, Rhidipurajavanica, and Accipiter soloensis.Based on data from survey and interview, it was revealed that seven trekking routes wereidentified in which birds were utilised as ecotour attractions or the routes of which have apotential to be developed as ecotour attractions (where birds utilised as their touristattractions in Ubud tourist resort and ajacent areas), such as: (1) Subak Sok Wayah Ubudand its surrounding areas; (2) Melinggih - Subak Kembang Kuning and their surroundingareas; (3) Laplapan, Banjar Sala and their surrounding areas; (4) Kliki (Bangkiang Sidem)and its surrounding areas; (5) Tirta Temple Mas Village and its surrounding areas; (6)Banjar Pande Peliatan Village - Alas Arum temple and their surrounding areas; (7) Petuluand its surrounding areas.Community perceptions on bird conservation and bird based ecotoursim in Ubud touristresort showed that: in general the community believed the need for conservation of birds,and they said that the development of bird based ecotour activities have given benefit for thecommunity, such as providing jobs and source of income for them, even though some constraintsstill need to be overcome, such as trekking trails that have not been perfect, the smell of fecesof birds, and weekness in human resources capability.From statements of stakeholders (community, govenment, industry, and visitors), it can berevealed that the commitment of all is needed in bird conservation, because they becomeimportant part of nature, in the sustainability of nature or ecosystem. The media for meetingand discussing for development of birds based tourism activities especially bird watching inUbud tourist resort need to be improved.Limitation in time may caused incompleteness of the bird data collected on this research. Asa result, a longer time in research is recommended. In addition, other studies or research arealso needed to get more data, the data of whcih their availability are still very limited. Forexample, research on bird habitats are also need to be undertaken.